2001
DOI: 10.1093/gerona/56.6.b268
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Effects of a Heterozygous Dnmt1 Null Mutation on Age-Dependent DNA Hypomethylation and Autoimmunity

Abstract: DNA methylation modifies gene expression. Methylation patterns are established during ontogeny, but they change with aging, usually with a net decrease in methylation. The significance of this change in T cells is unknown, but it could contribute to autoimmunity, senescence, or both. We examined the effects of a null mutation in DNA methyltransferase 1 (Dnmt1), a gene maintaining DNA methylation patterns, on immune aging. Whereas aged control mice developed hypomethylated DNA, autoimmunity, and signs of immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 34 publications
(39 reference statements)
1
22
1
Order By: Relevance
“…If AdoHcy is elevated in AdoHcy hydrolase-deficient patients during early gestation, as it was found to be in the cord blood of patient 2, the complex reprogramming of DNA methylation that occurs during embryonic development (Reik et al 2001) might be affected. A situation with certain similarities to that found in the present patients has been described by Yung and colleagues (Yung et al 2001). These authors found, surprisingly, that with age both lymphocyte and brain DNA became more methylated in mice heterozygous for a null mutation in DNA methyltransferase 1 (Dnmt1) than did the DNA of control mice.…”
Section: Metabolic Abnormalities and Changes During Therapysupporting
confidence: 87%
“…If AdoHcy is elevated in AdoHcy hydrolase-deficient patients during early gestation, as it was found to be in the cord blood of patient 2, the complex reprogramming of DNA methylation that occurs during embryonic development (Reik et al 2001) might be affected. A situation with certain similarities to that found in the present patients has been described by Yung and colleagues (Yung et al 2001). These authors found, surprisingly, that with age both lymphocyte and brain DNA became more methylated in mice heterozygous for a null mutation in DNA methyltransferase 1 (Dnmt1) than did the DNA of control mice.…”
Section: Metabolic Abnormalities and Changes During Therapysupporting
confidence: 87%
“…Interestingly, mouse knockout models for Dnmt1 and Dnmt3b have also shown defects in global DNA methylation (Yung et al 2001;Dodge et al 2005). Heterozygous Dnmt1 null mutation mice developed autoimmunity, although surprisingly, they displayed increased DNA methylation levels (Yung et al 2001). In humans, decreased levels of DNMT1 mRNA had previously been shown for T-cells isolated from SLE patients .…”
Section: Discussionmentioning
confidence: 96%
“…In parallel, a robust decrease in the global content of DNA methylation as well as a reduction of DNMT1 and DNMT3B mRNA levels were observed. Interestingly, mouse knockout models for Dnmt1 and Dnmt3b have also shown defects in global DNA methylation (Yung et al 2001;Dodge et al 2005). Heterozygous Dnmt1 null mutation mice developed autoimmunity, although surprisingly, they displayed increased DNA methylation levels (Yung et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We recently investigated the effect of DNA methylation in the development of autoimmunity in aging, by examining the effect of Dnmt1 deficiency on the development of autoimmunity in aging mice (71,72). While homozygous Dnmt1 knockout is embryonically lethal, young heterozygous animals have globally hypomethylated DNA and are phenotypically normal (73).…”
Section: Cross-talk Between Epigenetics Aging and Late-life Diseasesmentioning
confidence: 99%